Increasing Brand Trust through Marketing Communication and Its Impact on School principal's Loyalty - Nasib Nasib; Helena Louise Panggabean; Rafida Khairani; Zulia Rifda Daulay; Widy Hastuty HS (Budapest International Research and Critics University, 2021)
The purpose of this study is to determine the effect of communication marketing on school principal loyalty through brand trust. The approach in this research was quantitative. The data were obtained through a questionnaire with the Likert scaling technique. The population and sample in this study was 45 principals of high school, vocational and Aliyah private schools in Binjai and Langkat district. The sampling technique was accidental sampling was 45 respondents. The results showed that 1) marketing communication has a significant effect on brand trust. 2) Marketing communication has no effect on principal loyalty. 3) Student brand trust has a significant effect on the principal's loyalty. 4) Marketing communication has a significant effect on principal loyalty through brand trust.